'I Should Do Her Finger Here, on Her Cheek-Hmm, to Play or to Draw? That's How One Thinks': What Preschoolers Tell Us about Thinking through Drawing - Maria Papandreou; Anna Kalouda (MDPI AG, 2023)
As the importance of developing good thinkers from an early age is widely recognised as an overarching goal of contemporary early childhood curricula, research on nurturing children's thinking continues to grow. This study sought to gain insight into kindergarten children's understanding of the concept and process of thinking. A socio-cultural perspective that conceptualises thinking and its development as a dynamic, socially mediated process, in which signs, including drawing, guided the research. 35 children from Greece, aged 4-6 years, participated in the study and were involved in a drawing-telling activity. Thematic analysis, which included both the drawings and verbal responses of the participants, resulted in five main themes that reveal new aspects of children's perceptions and reflect the inherent complexity of the concept of thinking. Although the findings have direct implications for teaching and learning in early childhood classrooms, the discussion calls for further research in this area.